The Ark of Nabratein: A First Glance - Meyers, Eric M. (The Biblical archaeologist, 1981)
Current excavations of Galilean synagogues have led to the important discovery of an architectural fragment of a Torah Shrine, the successor to the ancient Ark of the Covenant in late Jewish tradition.